Generative AI. - Harvard Business Review Press (Boston, Massachusetts : Harvard Business Review Press, 2024)
"The world is stunned and transfixed by the marvel (and possible menace) of ChatGPT and other generative AI tools. It's clear that they will transform the business landscape-exactly when and how much are still to be seen. Meanwhile, your smartest competitors already navigating the risks and reaping the rewards of this new technology. They're trying out new business models around generating text and code at astonishing speed. They're automating customer interactions in ways that were never before possible. And they're augmenting human creativity innovate in new ways. How can you take advantage of generative AI and avoid having your business disrupted? Generative AI: The Insights You Need from Harvard Business Review will help you understand the potential of this new technology, pick the right generative AI projects, and reinvent your business for the new age of AI"--
Generative AI will change your business. Here's how to adapt : the race is on to see which brands can deliver / by David C. Edelman and Mark Abraham -- How network effects make AI smarter : more users means more data for algorithms to make better predictions / by Sheen S. Levine and Dinkar Jain -- A framework for picking the right generative AI project : how to identify the most valuable, and least risky, use cases for your company / by Marc Zao-Saunders and Marc Ramos -- How generative AI could disrupt creative work : three scenarios, and how to navigate them / by David De Cremer, Nicola Morini Bianzino, and Ben Falk -- How generative AI can augment human creativity : use it to promote divergent thinking / by Tojin T. Eapan, Daniel J. Finkenstadt, Josh Folk, and Lokesh Venkataswamy -- How generative AI will change sales : Microsoft and Salesforce have already rolled out sales-focused versions of this powerful tool / by Prabhakant Sinha, Arun Shastri, and Sally E. Lorimer -- Generative AI has an intellectual property problem : strategies to help companies mitigate the legal risk and ensure they're in compliance with the law / by Gil Appel, Juliana Neelbauer, and David A. Schweidel -- AI prompt engineering isn't the future : asking the perfect question is less important than really understanding the problem you're trying to solve / by Oguz A. Acar -- Eight questions about using AI responsibly, answered : how to avoid pitfalls around data privacy, bias, misinformation, generative AI, and more / by Tsedal Neeley -- Managing the risks of generative AI : guidelines for companies as they implement the next generation of AI tools / by Kathy Baxter and Yoav Schlesinger -- The AI hype cycle is distracting companies: by focusing on sci-fi goals, they're missing out on projects that create real value right now / by Eric Siegel.
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on March 11, 2024).
WorldCat record variable field(s) change: 050
Keywords: Artificial intelligence; Business -- Data processing; Success in business; Industrial management; Intelligence artificielle; Gestion -- Informatique; Succès dans les affaires; Gestion d'entreprise.; artificial intelligence; Artificial intelligence; Business -- Data processing; Industrial management; Success in business; elektronické knihy; electronic books